The Influence of Active Breaks on Neck Pain Relief in Office Settings: A Systematic Review - Mehdi Shakerkavar; Aistė Pažėrienė; Vilma Dudonienė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Non-specific neck pain (NSNP) is a prevalent musculoskeletal condition among office workers, primarily associated with prolonged static postures and sedentary work. Implementation of structured active or exercise breaks within the workday schedule have been suggested as a practical approach to alleviate the effects of prolonged sitting.